THEORETICAL ASPECTS OF DEVELOPMENT OF IDEAS OF A HUMAN RESOURCE IN MODERN ECONOMY - Y. Vnuchkov; S. Gubanova; L. Mikhailova (Вестник университета, 2018)
In this article the sequence of formation of ideas of a human resource of the modern organization is considered, the most significant steps of knowledge in the field and their entity are selected. The main concepts of control of human resources during different periods of historical development are systematized. Authors justified a thought that in today in a stage of formation there is a concept of control of the person and also the main views of control of human resources at the present stage of development are formulated.